RELATIONSHIP BETWEEN KNOWLEDGE, NUTRITIONAL ADEQUACY LEVEL, TEA DRINKING HABITS AND NUTRITIONAL STATUS WITH ANEMIA AMONG ADOLESCENT GIRLS IN SMK PRATAMA MULYA KARAWANG (STIKes Mitra Keluarga, 2021)
Introduction: Adolescent is a nation’s future asset that is prone to nutritional problems. One of the nutritional problem in adolescent is anemia. Anemia is a condition when the hemoglobin level is below normal limits. Currenty, anemia among adolescent is still a health problem both globally and in Indonesia. Anemia has a negative impact on adolescents, including reducing concentration in learning, reducing work productivity, and disrupting the body’s defense system. Furthermore, anemia is one of the indirect factors that cause maternal death. The prevalence of anemia among adolescent in Karawang Regency, especially at SMK Pratama Mulya Karawang is still quite high (53,3%), so it is necessary to do further research on the factors that influence the incidence of anemia among adolescent girls. This study aims to determine the relationship between knowledge, nutritional adequacy level, tea drinking habits, and nutritional status with incidence of adolescent girls anemia in SMK Pratama Mulya Karawang. Method: This study use a quantitative observational research with a cross sectional design. The minimum number of samples in this study was 65 people. Anemia data was collected using biochemical measurements of hemoglobin levels, knowledge data using a knowledge questionnare, nutritional intake data and tea drinking habits were carried out by interviewing using the SQ-FFQ form, while nutritional status data was measured by anthropometric measurements. Results: The results showed that there was a significant relationship between energy adequacy levels, protein adequacy levels, iron adequacy levels, and vitamin C adequacy levels with the incidence of anemia and there was no significant relationship between knowledge, vitamin B12 adequacy levels, tea drinking habits and nutritional status with the incidence of anemia in adolescent girls. Conclusion: Nutritional adequacy level is related to the incident of anemia among adolescent gils in SMK Pratama Mulya Karawang